Atomistic understanding of the coherent interface between lead iodide perovskite and lead iodide - Rothmann, MU; Lohmann, KB; Borchert, J; Johnston, MB; McKenna, KP; Herz, LM; Nellist, PD (Wiley, 2023)
Metal halide perovskite semiconductors have shown great performance in solar cells, and including an excess of lead iodide (PbI2) in the thin films, either as mesoscopic particles or embedded domains, often leads to improved solar cell performance. Atomic resolution scanning transmission electron microscope micrographs of formamidinium lead iodide (FAPbI3) perovskite films reveal the FAPbI3:PbI2 interface to be remarkably coherent. It is demonstrated that such interface coherence is achieved by the PbI2 deviating from its common 2H hexagonal phase to form a trigonal 3R polytype through minor shifts in the stacking of the weakly van-der-Waals-bonded layers containing the near-octahedral units. The exact crystallographic interfacial relationship and lattice misfit are revealed. It is further shown that this 3R polytype of PbI2 has similar X-ray diffraction (XRD) peaks to that of the perovskite, making XRD-based quantification of the presence of PbI2 unreliable. Density functional theory demonstrates that this interface does not introduce additional electronic states in the bandgap, making it electronically benign. These findings explain why a slight PbI2 excess during perovskite film growth can help template perovskite crystal growth and passivate interfacial defects, improving solar cell performance.